4x-5(3-3x)=x-7(4-x)-9

Simple and best practice solution for 4x-5(3-3x)=x-7(4-x)-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-5(3-3x)=x-7(4-x)-9 equation:



4x-5(3-3x)=x-7(4-x)-9
We move all terms to the left:
4x-5(3-3x)-(x-7(4-x)-9)=0
We add all the numbers together, and all the variables
4x-5(-3x+3)-(x-7(-1x+4)-9)=0
We multiply parentheses
4x+15x-(x-7(-1x+4)-9)-15=0
We calculate terms in parentheses: -(x-7(-1x+4)-9), so:
x-7(-1x+4)-9
We multiply parentheses
x+7x-28-9
We add all the numbers together, and all the variables
8x-37
Back to the equation:
-(8x-37)
We add all the numbers together, and all the variables
19x-(8x-37)-15=0
We get rid of parentheses
19x-8x+37-15=0
We add all the numbers together, and all the variables
11x+22=0
We move all terms containing x to the left, all other terms to the right
11x=-22
x=-22/11
x=-2

See similar equations:

| 3(7-x)-(x+2)=5+7(x-9) | | 3n-1=1/8 | | 21x/4-4/3=76 | | 5k−2=7 | | 2/3x+5/7=11/5(x+2) | | 5(z+6)=4(z-8)+z | | 27x+5=23.4x-1 | | 75+20x=35 | | 3x–1=6+2x | | 3m^2-2m+12=0 | | 24x-48÷6=4 | | 5x=11(2x-3)÷2 | | p+3=7-9p | | 12x2+24=0 | | 3x+1=11=2x | | 1/3(9x-12)-6x+15=-19 | | 95x=35x | | 5x=11(2x-3÷2) | | 7(5x-4)=3(8-5x) | | 8m-4=3+8 | | 5x-14+3x+2+x+32=180 | | 8w-8=4w-7 | | 90+5.45x=13.63x | | 4x-6+2x=2(3x-30 | | 5x=11(2x-3/2 | | 2x+6X+3X+8X+4=338 | | -4x+4/3=20 | | x+4X+X-20=180 | | (2y-12)=90 | | (X+2)+(2x+2)=4x+1x+2 | | 27x+5=-x+9.8 | | 20+9x=180 |

Equations solver categories